Early‐life environment and the risk of eczema at 2 years—Meta‐analyses of six Finnish birth cohorts. Issue 4 (7th April 2023) - Lukkarinen, Minna; Kirjavainen, Pirkka V.; Backman, Katri; Gonzales‐Inca, Carlos; Hickman, Brandon; Kallio, Sampo; Karlsson, Hasse; Karlsson, Linnea; Keski‐Nisula, Leea; Korhonen, Laura S.; Korpela, Katri; Kuitunen, Mikael; et al.
Abstract: Background: Urban‐related nature exposures are suggested to contribute to the rising prevalence of allergic diseases despite little supporting evidence. Our aim was to evaluate the impact of 12 land cover classes and two greenness indices around homes at birth on the development of doctor‐diagnosed eczema by the age of 2 years, and the influence of birth season. Methods: Data from 5085 children were obtained from six Finnish birth cohorts. Exposures were provided by the Coordination of Information on the Environment in three predefined grid sizes. Adjusted logistic regression was run in each cohort, and pooled effects across cohorts were estimated using fixed or random effect meta‐analyses. Results: In meta‐analyses, neither greenness indices (NDVI or VCDI, 250 m × 250 m grid size) nor residential or industrial/commercial areas were associated with eczema by age of 2 years. Coniferous forest (adjusted odds ratio 1.19; 95% confidence interval 1.01–1.39 for the middle and 1.16; 0.98–1.28 for the highest vs. lowest tertile) and mixed forest (1.21; 1.02–1.42 middle vs. lowest tertile) were associated with elevated eczema risk. Higher coverage with agricultural areas tended to associate with elevated eczema risk (1.20; 0.98–1.48 vs. none). In contrast, transport infrastructure was inversely associated with eczema (0.77; 0.65–0.91 highest vs. lowest tertile). Conclusion: Greenness around the home during early childhood does not seem to protect from eczema. In contrast, nearby coniferous and mixed forests may increase eczema risk, as well as being born in spring close to forest or high‐green areas.